Analysis of Import Gate Out Service Using Control Chart in PT Terminal Petikemas Surabaya - Rafly Septianarta Putra; Iis Dewi Ratih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Goods from abroad entering Indonesia must go through several stages of inspection. One of the final inspection stages of imported goods is through the import gate out of PT Terminal Petikemas Surabaya (PT TPS). Import Gate Out is the entry and exit access for each truck that will carry out activities in the area of PT TPS. The gate itself functions as a place to identify containers that will enter whether they are in accordance with the data and as a place of confirmation for the commanderer who will leave the port whether it has been completed and is in accordance with the existing procedures. In the import gate out process, there are operators in charge to ensure that the incoming or outgoing containers are in accordance with the existing system at PT TPS. In carrying out its duties, gate operators are expected to have the skills and speed to serve every container that will enter or leave PT TPS. To determine the extent of the performance duration of the gate operator PT TPS a research was conducted on the service time of the import gate out operator using descriptive analysis and control charts. This research was conducted using data collection techniques by observation. The results of this study indicate that the average transaction per day is 33.5 seconds.